The potential of effective microorganism (EM) inclusion in enhancing the properties of cement paste and concrete / Noorli Ismail - Ismail, Noorli (2019)
Recently, Effective Microorganism (EM) has shown the potential to be used as new additives in cement based materials. Previous research works reported the incorporation of EM increased the compressive and splitting tensile strength of cement based, significantly. However, extensive evaluation of other aspects need to be investigated to study their potential since the incorporation of EM in cement based materials is still new area. Experimental works in this present study showed the incorporation of EM in cement paste increased up to 40% compressive strength and leading to produce low porosity which decreased at least 19% corresponding to cement paste without EM. However, the hydration process was completed longer than specimens without EM due to the earlier reaction of dehydration and decarbonation detected using thermogravimetric (TGA/DTG) test and presence of potassium thulium chloride in EM solution. This can be a reasoning to the delayed initial and final setting time in the microbed cement paste. Furthermore, the high compressive strength and low porosity also leading to improve the internal densification of cement matrix which reported the formation of calcium silicate hydrate (CSH) and ettringite by detecting from formation of bundle shape and needles like pine leaves, acicular, thin, narrow and pointed shape, respectively at later age of 28 days and 60 days using scanning electron microscopy (SEM). The denser and lesser void in internal microstructure for the microbed cement paste also the factor contributes towards high compressive strength. Due to high resulted compressive strength, survivability of EM bacteria in cement paste was successfully detected using Biolog Microbial Identification System (BMIS) by the presence of EM bacteria species Microbacterium Flavescens, Leuconostoc Fallax and Achromobacter xylosoxidans which was able to survive up to 28 days in cement paste. Subsequently, the establishment of relationship between compressive strength and total porosity was established for low, normal and high concrete at the age of 3, 28, 60 and 180 days. Incorporation of EM also produce lower porosity of concrete which was conducted by mercury intrusion porosimetry (MIP). Also the relationship of compressive strength from destructive and non-destructive tests was successfully established.